EFFORTS TO INCREASE ACTIVITY AND RESULTS OF MATH STUDENTS LEARNING THROUGH APLICATION MODEL MAKE A MATCH TYPE COOPERATIVE LEARNING PRIMARY CLASS VI SD NEGERI 168432 TEBING TINGGI - Nurainun Harahap (FIP Unimed, 2017)
The research aims to find out student learning activities, and improve student learning outcomes by applying cooperative learning model Type Make A Match on classroom material of class VI circle of 38 students. The object of this research is the application of Cooperative Learning Model Type Make A Match (looking for partner). This study is a classroom action research. To obtain data in this research used observation sheet and test result of student learning in the form of objective test as much as 5 problem esay. In this study used 3 cycles, consisting of 4 stages, namely planning, implementation, observation, and reflection. Activity and result of learning mathematics before applied model of Cooperative Learning Type Make A Match. Keywords: Activity, Co-operative Learning, Make A Match ABSTRAKPenelitian bertujuan untuk mengetahui aktivitas belajar siswa, dan peningkatan hasil belajar siswa dengan menerapkan model pembelajaran Kooperatif Tipe Make A Match pada materi luas lingkaran kelas VI sebanyak 38 siswa. Objek dalam penelitian ini adalah penerapan model pembelajaran Kooperatif Tipe Make A Match (mencari pasangan). Penelitian ini adalah penelitian tindakan kelas. Untuk memperoleh data dalam penelitian ini digunakan lembar observasi dan tes hasil belajar siswa berupa tes objektif sebanyak 5 soal esay. Dalam penelitian ini digunakan 3 siklus, yang terdiri dari 4 tahap, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Aktivitas dan hasil belajar matematika sebelum diterapkan model pembelajaran Kooperatif Tipe Make A Match. Kata Kunci : Aktifitas, Model Kooperatif, Make A Match